Update on the genetics of the epilepsy‐aphasia spectrum and role of GRIN2A mutations. (18th May 2020) - Lesca, Gaetan; M⊘ller, Rikke S.; Rudolf, Gabrielle; Hirsch, Edouard; Hjalgrim, Helle; Szepetowski, Pierre
Abstract: Formerly idiopathic, focal epilepsies (IFE) are self‐limiting, "age‐related" diseases that mainly occur during critical developmental periods. Childhood epilepsy with centrotemporal spikes, or Rolandic epilepsy (RE), is the most frequent form of IFE. Together with the Landau‐Kleffner syndrome and the epileptic Encephalopathy related to Status Epilepticus during slow Sleep syndrome (ESES), RE is part of a single and continuous spectrum of childhood epilepsies and epileptic encephalopathies with acquired cognitive, behavioral and speech and/or language impairment, known as the epilepsy‐aphasia spectrum (EAS). The pathophysiology has long been attributed to an elusive and complex interplay between brain development and maturation processes on the one hand, and susceptibility genes on the other hand. Studies based on the variable combination of molecular cytogenetics, Sanger and next‐generation sequencing tools, and functional assays have led to the identification and validation of genetic mutations in the GRIN2A gene that can directly cause various types of EAS disorders. The recent identification of GRIN2A defects in EAS represents a first and major break‐through in our understanding of the underlying pathophysiological mechanisms. In this review, we describe the current knowledge on the genetic architecture of IFE.